Time Series And Cross-Section Analysis On The Financial Performance Of PT Matahari And PT ACE Hardware For The 2021–2024 Period - Maslina Samosir; Maria Kalista Lambo; Cholis Hidayati (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study aims to analyze and compare the financial performance of PT Matahari Department Store Tbk and PT ACE Hardware Indonesia Tbk during the 2021–2024 period. The approach used is quantitative with a type of comparative research, using secondary data in the form of financial ratios sourced from the financial statement analysis documents of each company. The analysis was carried out through the time series method to see the development of performance from year to year and the cross-section method to compare the performance of the two companies in the same period. The financial ratios analyzed include liquidity, activity, solvency, and profitability ratios. The results of the study show that PT Matahari is experiencing great pressure on liquidity and solvency aspects which are characterized by negative net working capital and a very high level of debt dependence due to a decrease in equity. The efficiency of PT Matahari's asset utilization shows improvement, but this condition has not been able to cover the financial risks faced. PT ACE Hardware showed a more stable financial performance with consistent profit and equity growth, a strong capital structure, and maintained profitability. The results of the comparison show that PT ACE Hardware has a healthier and more sustainable financial performance than PT Matahari during the study period. This research is expected to be a reference for company management, investors, and academics in assessing the financial health of retail companies in Indonesia.